2008
DOI: 10.1029/2008tc002269
|View full text |Cite
|
Sign up to set email alerts
|

Paleogene building of the Bolivian Orocline: Tectonic restoration of the central Andes in 2‐D map view

Abstract: Using available information on the magnitude and age of tectonic shortening, as well as paleomagnetically determined tectonic rotations, we have run a series of 2‐D map view restorations of the central Andes. Neogene shortening in the foreland belt induced only slight orogenic curvature of the central Andes. The constraints on the ages of the large observed fore‐arc rotations (average of 37° counterclockwise in southern Peru and 29° clockwise in northern Chile) indicate that the Bolivian Orocline formed during… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

20
180
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 137 publications
(203 citation statements)
references
References 92 publications
20
180
1
Order By: Relevance
“…Deformation in the Eastern Cordillera almost ceased between 12 and 8 Ma, with the formation of the San Juan de Oro surface and the initiation of the Subandean fold and thrust belt (Gubbels et al, 1993;Somoza et al, 2002;Somoza and Tomlinson, 2002a;Oncken et al, 2006). In coincidence with these observations, Arriagada et al (2008a) noted that Incaic deformation concentrated along the Chilean Precordillera and the Eastern Cordillera of southern Bolivia and northwestern Argentina. Deformation in the Chilean Precordillera began in the Late Cretaceous and peaked between ~45 and ~32 Ma, while shortening in the Eastern Cordillera occurred mainly in the Paleogene-Early Miocene, starting at ~45-40 Ma (Arriagada et al, 2008a).…”
Section: Structural Developmentsupporting
confidence: 48%
See 1 more Smart Citation
“…Deformation in the Eastern Cordillera almost ceased between 12 and 8 Ma, with the formation of the San Juan de Oro surface and the initiation of the Subandean fold and thrust belt (Gubbels et al, 1993;Somoza et al, 2002;Somoza and Tomlinson, 2002a;Oncken et al, 2006). In coincidence with these observations, Arriagada et al (2008a) noted that Incaic deformation concentrated along the Chilean Precordillera and the Eastern Cordillera of southern Bolivia and northwestern Argentina. Deformation in the Chilean Precordillera began in the Late Cretaceous and peaked between ~45 and ~32 Ma, while shortening in the Eastern Cordillera occurred mainly in the Paleogene-Early Miocene, starting at ~45-40 Ma (Arriagada et al, 2008a).…”
Section: Structural Developmentsupporting
confidence: 48%
“…Isacks (1988) presented a regional oroclinal model, suggesting that an ancient curvature of the margin was enhanced to accommodate along-strike gradient of Neogene horizontal-shortening in the eastern part of the Central Andes. However, Arriagada et al (2008a) ran a 2-D map view restoration experiment using first-order constraints on the magnitude and age of shortening and rotations in the Central Andes, and concluded that the Arica Deflection formed during the EoceneOligocene as a consequence of differential shortening focused in the Eastern Cordillera. According to these authors, Neogene shortening in the sub-Andean zone only slightly enhanced the orogenic curvature of the Central Andes.…”
Section: Introductionmentioning
confidence: 99%
“…The targeted situations include the deformation of the fore-arc, arc and back-arc along a seaward-concave plate boundary such as in the central Andes. The deformation near the symmetry axis is fundamentally three-dimensional with both trench-parallel and trenchperpendicular normal shortening (Kley, 1999;Hindle et al, 2002Hindle et al, , 2005Arriagada et al, 2008), and is most likely due to the stress conditions along the plate boundary. We have shown that we can estimate these stress conditions in our analogue models using simple cylindrical experiments.…”
Section: Resultsmentioning
confidence: 99%
“…For example, kinematic models of the Andes show that trenchparallel normal shortening as well as trench-perpendicular normal shortening existed in the center of the plate boundary curvature while the Andes were built (Kley, 1999;Hindle et al, 2002Hindle et al, , 2005Oncken et al, 2006;Arriagada et al, 2008;Gotberg et al, 2009). Two-dimensional, numerical simulations reveal that trench-parallel compression is produced near the symmetry axis of a seaward-concave plate boundary if interplate friction is high and/or the subducting lithosphere has a low flexural rigidity (Boutelier and Oncken, 2010).…”
Section: Imposing a Subduction Regime In Non-cylindrical Thermo-mechamentioning
confidence: 99%
“…In the other hand, the Paleogene deformation is more widely distributed across the Andes of northern Chile (Arriagada et al, 2000(Arriagada et al, , 2003(Arriagada et al, , 2006bTaylor et al, 2007). Eocene-Oligocene deformation was accompanied by tectonic shortening, mountain uplift and significant clockwise block rota tions (e.g., Hartley et al, 1992;Riley et al, 1993;Forsythe and Chisholm, 1994;Randall et al, 1996;Taylor et al, 1998;Arriagada et al, 2000;Somoza and Tomlinson, 2002;Arriagada et al, 2003Arriagada et al, , 2006bArriagada et al, , 2008. Fission track thermochronology indicates that tectonic uplift and erosion were mainly active during the EoceneEarly Oligocene 'Incaic Orogeny', when at least 4-5 km of rocks were eroded during exhumation of tectonic blocks of the Cordillera de Domeyko between ca.…”
Section: Introductionmentioning
confidence: 99%